G : Material zur elementaren Gestaltung (ondertitel varieert: Zeischrift für elementare Gestaltung (vanaf Nr. 3)) = G : Material for Elemental Form-Creation (2011) - Richter, Hans; Graeff, Werner; El Lissitzky (Berlin : Friedenau, 1923)
Avant-garde journal edited and published in Berlin by Hans Richter. Five issues were produced in German between 1923-26. El Lissitzky and Werner Graeff were on the editorial board of the first issue, subsequently the architects Ludwig Mies van der Rohe and Kiesler joined Richter as editors. (https://monoskop.org/G)
Zie: http://www.dada-companion.com/journals/per_g.php
Online: https://monoskop.org/G
Tijdschriften
Keywords: 20ste eeuw; avant-garde.; dadaïsme; constructivisme